2011
DOI: 10.1093/brain/awr093
|View full text |Cite
|
Sign up to set email alerts
|

Disability, atrophy and cortical reorganization following spinal cord injury

Abstract: The impact of traumatic spinal cord injury on structural integrity, cortical reorganization and ensuing disability is variable and may depend on a dynamic interaction between the severity of local damage and the capacity of the brain for plastic reorganization. We investigated trauma-induced anatomical changes in the spinal cord and brain, and explored their relationship to functional changes in sensorimotor cortex. Structural changes were assessed using cross-sectional cord area, voxel-based morphometry and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
269
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 248 publications
(303 citation statements)
references
References 51 publications
28
269
5
1
Order By: Relevance
“…23,24 We did not find any significant differences in the DTI metrics between SCI patients and controls in these structures. Freund et al 14 and Guleria et al 15 showed reduced FA values but unchanged MDs in the PLIC after SCI compared with healthy subjects. Guleria et al 15 reported a progressive increase in the FA values in the PLIC and corona radiata up to 12 months after injury.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…23,24 We did not find any significant differences in the DTI metrics between SCI patients and controls in these structures. Freund et al 14 and Guleria et al 15 showed reduced FA values but unchanged MDs in the PLIC after SCI compared with healthy subjects. Guleria et al 15 reported a progressive increase in the FA values in the PLIC and corona radiata up to 12 months after injury.…”
Section: Discussionmentioning
confidence: 96%
“…Freund et al 14 and Guleria et al 15 showed reduced FA values but unchanged MDs in the PLIC after SCI compared with healthy subjects. Guleria et al 15 reported a progressive increase in the FA values in the PLIC and corona radiata up to 12 months after injury. FA values in the corona radiata were eventually higher in subjects with SCI compared with the controls.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations